Dosing patterns of three tumor necrosis factor blockers among patients with rheumatoid arthritis in a large United States managed care population. (May 2013) - Fisher, Maxine D.; Watson, Crystal; Fox, Kathleen M.; Chen, Yen-Wen; Gandra, Shravanthi R.
Abstract Objective: To describe dosing patterns of etanercept, adalimumab, and infliximab in rheumatoid arthritis (RA) patients in US managed care. Methods: This retrospective analysis included adult (18–64 years) RA patients in the HealthCore Integrated Research Database with ≥1 claim for etanercept, adalimumab, or infliximab between 7/1/2007 and 1/31/2010. Patients had 6 months pre-index and 12 months post-index claim eligibility. Patients without any TNF blocker claim during the pre-index period were considered new patients and patients with a TNF blocker claim during the pre-index period were considered continuing patients. Persistence, discontinuation, switch, and dose escalation patterns were evaluated. Patients with 1-year persistence were evaluated for dose escalation using two methods: (1) average weekly dose and (2) increase from 50 mg to 75 mg or 100 mg weekly of etanercept or from 40 mg every other week to 40 mg weekly of adalimumab or increase in vial or decreased infusion interval for infliximab. Results: Data from 2426 patients were analyzed (1595 etanercept; 417 adalimumab; 414 infliximab). Persistence ≥1 year on index medication was reported in 62.2% and 89.2% of new and continuing patients on etanercept, respectively, 66.0% and 94.0% on adalimumab, and 68.9% and 96.4% on infliximab. Discontinuation occurred in 19.7% and 7.9% of new and continuing patients on etanercept, respectively, 20.6% and 4.5% on adalimumab, and 18.8% and 2.1% on infliximab. Switching occurred in 12.2% and 4.3% of new and continuing patients on etanercept, respectively, 9.1% and 1.8% on adalimumab, and 10.4% and 2.1% on infliximab. Dose escalation was lower with etanercept (0.4–2.6%) than adalimumab (12.6–24.3%) or infliximab (40.0–79.5%) (P < 0.0001). Conclusions: Discontinuation and switching were common within 1 year of initiating etanercept, adalimumab, and infliximab in patients with RA in this analysis. Study limitations included the restricted patient age range; analysis of three TNF blockers; study period (prior to approval of additional agents); and missing reasons for treatment changes.